Artificial Intelligence dalam Perspektif Al-Qur’an: Telaah Etika, Ontologi, dan Batasan Kemanusiaan - Husni Husni Mubaraq (Al-Widad, 2025)
Ideally, the development of Artificial Intelligence (AI) serves as a tool to enhance human capacity in thinking, working, and making decisions more effectively. However, in reality, the advancement of AI brings significant ethical and ontological challenges, including the potential loss of human autonomy, algorithmic bias, and concerns that the boundary between machine intelligence and human consciousness is becoming increasingly blurred. Therefore, a guiding value framework is needed to properly position intelligent technologies within modern life. The Qur’anic perspective offers a relevant conceptual foundation for understanding human uniqueness and the limitations of all non-human creations. This study aims to examine AI through the dimensions of ethics, ontology, and human boundaries by analyzing Qur’anic verses related to intellect, creation, and moral responsibility. The research employed a qualitative library-based method, using thematic analysis of primary and secondary sources. The findings indicate that the Qur’an emphasizes the uniqueness of humans as rational and moral beings, while AI remains an instrumental creation without consciousness. Principles such as justice, public benefit (maslahah), and the preservation of human dignity serve as essential foundations for the responsible development and application of AI.